DARI TOLERANSI KULINER HINGGA POLITIS: PROSES INKULTURASI TIONGHOA MENJADI JAWA MASYARAKAT TIONGHOA BALONG SURAKARTA PARUH KEDUA ABAD XX - Riyadi, Riyadi (Candi, 2014)
This article is an attempt to explore the social history of Chinese community in Kampong Balong Surakarta in the social interaction with Javanese in the second half of twentieth century. This article is based on that the history of lower-class Chinese community is generally entrapped in two things: generalization of majority Chinese or forgotten in the history. The problem of research is that there is a series of natural processes to become Javanese proceeding among the Chinese, as well as there is always harmony relationship between those two ethnics along the history.Social change is caused by the mixed marriage with the Javanese or other ethnics as well as the acceptance of assimilation policy during New Order time. This series of changes show the process ?of becoming Javanese?, despite the Chinese culture revival in the twentieth century, along with the governmental policy at that time. Keywords: Chinese ethnic, Social Life, Kampong Balong Surakarta